2020
DOI: 10.2499/9780896293946
|View full text |Cite
|
Sign up to set email alerts
|

2020 Annual trends and outlook report: Sustaining Africa's agrifood system transformation: The role of public policies

Abstract: Established in 2006 under the Comprehensive Africa Agriculture Development Programme (CAADP), the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) supports efforts to promote evidence-and outcome-based policy planning and implementation. In particular, ReSAKSS provides data and related analytical and knowledge products to facilitate CAADP benchmarking, review, and mutual learning processes. AKADEMIYA2063 leads the work of ReSAKSS in partnership with the African Union Commission, the African U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 297 publications
(397 reference statements)
0
7
0
Order By: Relevance
“…This trend is removed from our data before our correlation analyses to effectively remove the effect of non-climatic factors. Previous research analyzing the causes of agricultural production growth in SSA argued that production increases have occurred in the past irrespective of rainfall conditions (Resnick et al 2020). An alternative approach using the significance of the relationship between iNDVI and the climate variables precipitation, temperature, and solar radiation to determine whether climate or non-climatic factors drive trends in iNDVI found that our study area experienced a non-climatic browning trend from 2000-2018 (Mechiche-Alami and Abdi 2020).…”
Section: Non-climatic Factors To Maize Yield Growthmentioning
confidence: 90%
See 2 more Smart Citations
“…This trend is removed from our data before our correlation analyses to effectively remove the effect of non-climatic factors. Previous research analyzing the causes of agricultural production growth in SSA argued that production increases have occurred in the past irrespective of rainfall conditions (Resnick et al 2020). An alternative approach using the significance of the relationship between iNDVI and the climate variables precipitation, temperature, and solar radiation to determine whether climate or non-climatic factors drive trends in iNDVI found that our study area experienced a non-climatic browning trend from 2000-2018 (Mechiche-Alami and Abdi 2020).…”
Section: Non-climatic Factors To Maize Yield Growthmentioning
confidence: 90%
“…Hollinger and Staatz (2015) attribute WA's yield growth to increased use of fertilizers and improved varietals. However, Resnick et al (2020) argues that fertilizer use remains low and could be better-targeted to local needs, which limits its impact on yields. Instead, current policy reforms and improved economic governance in the region has allowed the region's production to take advantage of opportune rain and market conditions (Resnick et al 2020).…”
Section: Non-climatic Factors To Maize Yield Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, unpredictable trade policies like short-term export bans are common 3,23 , reducing incentives for traders to invest in durable trade networks 30 . Accelerated development along the whole food supply chain is needed to improve the competitiveness of agriculture in Africa 5,15 . A first crucial element is agricultural productivity growth, for which especially in Sub-Saharan Africa the potential is huge 2,31 .…”
mentioning
confidence: 99%
“…To inform policy implementation, we therefore assess also the prioritization of individual measures of trade liberalization, facilitation, and development (decomposition of the main scenarios), as well as the prioritization of agricultural investments in certain locations (Connect scenario) or sectors (Food and Export scenario). Prioritization may not only be necessary given constraints on financial resources, but also to harmonize tradeoffs across different policy objectives, for example between food security and environmental impacts 15 . The scenarios results are presented as compared to a baseline that is quantified according to the second Shared Socio-Economic Pathway (SSP2) 55 in which local and international trade costs remain constant and crop yields develop according to historical trends.…”
mentioning
confidence: 99%